Africa Bibliography (Cambridge)
The Africa Bibliography includes a wide range of material: monographs, chapters in edited volumes, journal articles, and pamphlets. It covers all regions of Africa, including North Africa. It lists works published in English as well as a number of other languages: Portuguese, French, Italian, German, Swahili, Spanish and Afrikaans. The bibliography categorises by region, country and subject. It includes an author index and a detailed thematic index.
Keywords: Bibliography